2007
DOI: 10.1200/jco.2007.10.6450
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Individual Risk for Prostate Cancer

Abstract: In a PC screening program, it is important to consider age, family history of PC, ethnicity, urinary voiding symptoms, and free:total PSA ratio, in addition to PSA and DRE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 30 publications
2
119
1
1
Order By: Relevance
“…Although use of any particular cutoff point for PSA is not established as optimal, the recognition that many patients with a serum PSA over 2.5 ng ml À1 have prostate cancer makes discussion of prostate cancer risks with an informed provider necessary. 12,[17][18][19] There are several interesting findings in this study. First, non-urologist physicians ordered PSA tests on 2884 men in 1 year's time at our institution.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although use of any particular cutoff point for PSA is not established as optimal, the recognition that many patients with a serum PSA over 2.5 ng ml À1 have prostate cancer makes discussion of prostate cancer risks with an informed provider necessary. 12,[17][18][19] There are several interesting findings in this study. First, non-urologist physicians ordered PSA tests on 2884 men in 1 year's time at our institution.…”
Section: Discussionmentioning
confidence: 95%
“…Risk calculators have been developed which use these personalized values in place of relying on a generalized threshold value, and are freely available online. [17][18][19][20] This type of patient-oriented, tailored approach which eliminates traditional thresholds may assist in the dialogue between physician and patient on what course of management is best for that particular patient, on the basis of evidence-based medicine and the informed patient's personal preference.…”
Section: Introductionmentioning
confidence: 99%
“…The Sunnybrook risk calculator was developed using clinical data from 3,108 Canadian men and utilize PSA, percent free PSA, age, family history, race, International Prostate Symptom Score, and DRE [71]. This tool assesses risk for any cancer and high-grade (Gleason score ≥7) disease and has reportedly fairly high accuracy for predicting either event (AUC 0.74 and AUC 0.77, respectively) [71].…”
Section: Integrated Prediction Of Prostate Cancer Riskmentioning
confidence: 99%
“…This tool assesses risk for any cancer and high-grade (Gleason score ≥7) disease and has reportedly fairly high accuracy for predicting either event (AUC 0.74 and AUC 0.77, respectively) [71]. The original investigators later performed a prospective, multiinstitutional evaluation and found the Sunnybrook calculator to outperform the PCPT in terms of predicting any disease (AUC 0.67 vs. 0.61), as well as aggressive disease (AUC 0.72 vs. 0.67) [65•].…”
Section: Integrated Prediction Of Prostate Cancer Riskmentioning
confidence: 99%
“…Currently, a common method for the detection of prostate cancer is a blood test known as the prostate specific antigen test. However, doubts have been raised about the accuracy and usefulness of this test (Nam et al 2007). Another test is the digital rectal exam which measures the size and texture of the prostate gland manually (Chodak et al 1989).…”
Section: Introductionmentioning
confidence: 99%